Pengaruh Komunikasi Pemasaran, Kualitas Produk, dan Label Halal terhadap Keputusan Pembelian di TikTok Shop - Elizabeth; Pradiptha, Anindya Putri; Setiono, Devit; Putra, Dhika Purnama; Putra, Ricky Widyananda (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
TikTok is a effective medium to promote and selling product. Because Tiktok has hundred of thousand users, which of course makes the product known to various group. This application has been successfully used by various brand to promote their products to consumers, especially to cosmetic industry, both local product and international brand. One of local product that dominates market share is Wardah Kosmetik as with its trademark as halal cosmetics. This study aims to analyze and examine the factors influence consumer purchase decisions Wardah Lipstick products of TikTok aplication users. These factors include the product quality, promotion and halal label. The research used the quantitative with regression analysis method. The sampling method used purposive sampling and the number of samples used in this study amounted to 75 respondents source was distribution of questionnaires to TikTok users in Central Lombok by online via WhatsApp. The data were analysed with IBM SPSS version 21 and analysis was carried out by several tests such as validity test, realibility test, classic assumption test, linear regression analysis and coefficient of determination test. The results of this study indicate that the product quality, promotion and halal label has a significant effect on purchase decisions Wardah Lipstick products of TikTok aplication users. The findings of this study can be reference uses as a reference for future researchers who will study similar problems. This research can also be a reference for companies to always be able to maintain aspects of product quality, promotion and halal label in designing and determining effective and efficient markering policies.